As políticas públicas municipais para a educação de crianças de zero a três anos na cidade de São Carlos: um estudo sobre o período de 1977 a 2006, a partir das falas de agentes do Estado - Tebet, Gabriela Guarnieri de Campos (2007)
This work discourses on the municipal public politics for the education of children from zero to three years in the city of São Carlos, configuring itself as a study on the period of 1977 to 2006, carried out through the speeches of State agents. It presents brief history of this town, the influence of the doctor-hygienism in the children's education and characterizes and discuss the type of attendance offered at the daycare centers in São Carlos as well as the public politics oriented to children from zero to three years old in distinct moments in the city's history and raises questions concerning to the children education that has been nationaly discussed, but that in this work appear from the analysis of the local experience of infancy support. The proposed analysis for this work was done based on the history of the day-care centers of São Carlos in three periods: i) previous to the 1977, intitled, in this work as the "Philantroply's Period ", ii) between the years of 1977 and 1996, intitled as the "Assistance's Period" and iii) between the years of 1997 and 2006, intitled as the "Education's Period"